Perhatian Orang Tua terhadap Prestasi Belajar Siswa - Siti Sholekah; Titin Swastinah; Masjkur Masjkur (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2019)
Improving the quality of education for the people of Indonesia is an issue that always gets attention essential for the implementation of community development f a country. Problem in this research is there any influence of parent’s attention on student achievement Elementery School fifth grade Ampel 04 Wuluhan – Jember 2018/2019 school year. Research using questionnaires, observation, documentation, and interviews to obtain data, and the analyzed using product moment correlation, an tested with the level of 5% N=22 at 0,404 and level 1% of 0,515. 0,12 rxy result is much lower than rt product moment. In this case, HA HO rejected an accepted. Of these results prove no influence parent’s attention on student achievement Elementery School fifth grade Ampel 04 Wuluhan-Jember 2018/2019 school year with a significant level is very low. Keywords: Attention Parents, Academic Achievement